Improving objectivity in assessing community empowerment grant proposals - Shukor, Nurul Naqirah Binti; Zahari, Haliza Mohd; Wong, Mohd Muhaimin Ridwan; Ahmad, Noor Diyana Fazan; Abas, Fuad; Husin, Wan Norhasniah Wan (International Journal of Studies in Social Sciences and Humanities (IJOSSH), 2024)
Community empowerment grants is one of many initiatives by the Malaysian government to foster social change, economic development and environmental sustainability at the grassroots' level. Annually, the government through its many ministries offer such grants to non-governmental organisations (NGOs) for community program implementations with a predefined aim, scope and target beneficiaries. Analysis of relevant documents, in-depth interviews and focus group discussions involving representatives of Jabatan Pendaftaran Pertubuhan Malaysia (JPPM) and local NGOs is the qualitative method used to enhance the evaluation of community program grant proposals, particularly with the aim to ensure objectivity, fairness and transparency. In this paper, preliminary studies for developing scoring rubric to address the above issue, drawing from extensive review of current practices and responses received from both the government and the NGOs. The assessment is designed around dimensions of community empowerment deliverables, measurable outcomes, implementation capacity, risk management, and program sustainability, each with their own set of indicators. Additionally, this paper also explored the challenges and potential for the application of the scoring rubric for different type of grants, projects or users. In conclusion, by providing a clear and consistent tool to evaluation community program proposals, it is believed that the decision-making and evaluation processes for public-funded community programs, and subsequently the positive impact of such initiatives by the government can be further improved.